Research advancement of Apostichopus japonicus from 2000 to 2021 - Chen, Jiting; Lv, Zhimeng; Guo, Ming (Frontiers in Marine Science, 2022)
This study aims to establish a quantitative and qualitative evaluation model of sea cucumber Apostichopus japonicus research. Data from 2000 to 2021 were obtained from the Web of Science Core Collection (WoSCC) of Thomson Reuters. Bibliometrics and CiteSpace software were used to analyze authors, exporting countries, journals, influential articles, research areas, institutions, research hot spots, and trends. A total of 1,358 research papers on A. japonicus research were identified from 2000 to 2021. The number of papers published in this field is rapidly increasing, and the research phase can be divided into initial, developmental, and stabilization phases. Research on A. japonicus is mostly conducted in China, followed by Japan and the United States. Hongsheng Yang, Chenghua Li, and Shuanglin Dong are the lead authors. Research activities are focused on genetics and breeding, growth and development, immunology and disease, aestivation, regeneration, and food processing. Gut microbiota, activation, and collagen are potential research hot spots. The project highlights differences in the level of research between countries and teams, and regions with more developed industries or richer resources need further support. Governments or organizations are encouraged to 1) promote the development of the A. japonicus industry through the development or implementation of policies; 2) further participate in the research, production, and processing of A. japonicus; and 3) strengthen international exchange and cooperation to bring economic benefits to farmers in suitable breeding areas through technology sharing.